Post colonialism discourse and novel “Khai Chaand Thay Sare-Asmaah” - Yousuf Noon; Qasim, Muhammad; Ahmad, Gulzar (Zaban-o-Adab, 2023)
The novel of Shams-ur-RehmanFarooqi "Kayi Chand Thy Sare-Assmaah" depicts the culture of Hindu Muslim In the nineteenth Century, The focus of the article is on the occupation of sub continent by English imperialism. The character of the local resident WazirKhanam, the attitude of colonizers and exploitation of the local residents are the main topics of the novel. Different instances have been added to explain post colonialism. The colonizers, by their civilization make the local residents mentally slave. They trap the local women and get access to their bodies. Wazirkhanam is the heroin of " Kayi Chand Thy Sare-Assmaah" Shams-ur-Rehman want to explain different aspects through the character of WazirKhanam. The colonizers Captured the Sub Continent and they affected the lives of the local residents. They Captured the civilization of the subcontinent. They also used the local people and their resources to set industry and to strength their financial position in Britain.